Kebijakan Penataan Sempadan Sungai Cisadane di Kota Tangerang (Penanganan Penyalah Gunaan Lahan di Kelurahan Babakan dan Kelurahan Mekarsari) - Ryan Fadhillah Irawan; Wiwik Widayati; Turtiantoro . (Journal of Politic and Government Studies, 2014)
AbstractAs an Industrial based city and have been decided to be the National Strategic Area, The City of Tangerang has become the one of favorite place to seek a job. With the job seekers from all over Indonesia and the people who already lives in Tangerang as a local society, are escalating with the demands of land for residence. In the end, some of the people are illegally using the government property (land(s),river,etc.) such as Cisadane river in sempadan. Its problem are spreading to the other area such as Babakan Village, Tangerang Sub-District, and Mekarsari Village, Negrasari Sub-District.Based on the field report and analyzing the main purpose of Cisadane River, Tangerang Government’s along with the National Government are having the policy to make a maintenance of Cisadane river, and the people who lives in the area of Cisadane river has been warn to leave.The policy are not fully worked, there is a refusal from the people who lives in the area of Cisadane river. The Tangerang Government’s are taking the legal act as a main plan, but the problems are slowly sprung, and the maintenance program of Cisadane river in Mekarsari Village, Neglasari Sub-District are stopped until undecided time limit.The law must been stake, but the Tangerang Government’s need the other kind of approaching to the people, and still could applicating the policy that been stated, so the policy would reach the main purpose and advantageous to the people of Tangerang City.Keywords : The City of Tangerang Government’s, The warn of Sempadan’s Cisadane river, Squatter Settlement .